Mechanical and chemical unfolding of a single protein: A comparison - Carrion-Vazquez, Mariano (The National Academy of Sciences, 1999)
Is the mechanical unraveling of protein domains by atomic force microscopy (AFM) just a technological feat or a true measurement of their unfolding? By engineering a protein made of tandem repeats of identical Ig modules, we were able to get explicit AFM data on the unfolding rate of a single protein domain that can be accurately extrapolated to zero force. We compare this with chemical unfolding rates for untethered modules extrapolated to 0 M denaturant. The unfolding rates obtained by the two methods are the same. Furthermore, the transition state for unfolding appears at the same position on the folding pathway when assessed by either method. These results indicate that mechanical unfolding of a single protein by AFM does indeed reflect the same event that is observed in traditional unfolding experiments. The way is now open for the extensive use of AFM to measure folding reactions at the single-molecule level. Single-molecule AFM recordings have the added advantage that they define the reaction coordinate and expose rare unfolding events that cannot be observed in the absence of chemical denaturants.